2013
DOI: 10.1073/pnas.1215156110
|View full text |Cite
|
Sign up to set email alerts
|

FCRL5 exerts binary and compartment-specific influence on innate-like B-cell receptor signaling

Abstract: Innate-like splenic marginal zone (MZ) and peritoneal cavity B1 B lymphocytes share critical responsibilities in humoral responses but have divergent B-cell receptor (BCR) signaling features. A discrete marker of these subsets with tyrosine-based dual regulatory potential termed "Fc receptor-like 5" (FCRL5) was investigated to explore this discrepancy. Although FCRL5 repressed the robust BCR activity that is characteristic of MZ B cells, it had no influence on antigen receptor stimulation that is blunted in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 66 publications
3
45
0
Order By: Relevance
“…Initial work in WEHI231 and primary MZ B cells showed that FCRL5 also inhibits BCR-mediated calcium signaling (Won et al, 2006), but surprisingly had little impact on activation in innate-like B1 B cells that also discretely express it. As in earlier work (Ehrhardt et al, 2003), we engineered a panel of chimeric receptor mutant constructs comprised of the extracellular and transmembrane portions of mouse FcγRIIB fused to different FCRL5 Y>F tail variants for transduction into the FcγR deficient IgG2a class-switched A20IIA1.6 B cell line (Zhu et al, 2013). This system permits a comparative analysis of downstream signaling pathways engendered by chimeric receptor/BCR co-engagement by using intact anti-mouse IgG versus BCR-only triggering using F(ab’)2 fragments (Okazaki et al, 2001).…”
Section: Functional and Regulatory Propertiesmentioning
confidence: 99%
“…Initial work in WEHI231 and primary MZ B cells showed that FCRL5 also inhibits BCR-mediated calcium signaling (Won et al, 2006), but surprisingly had little impact on activation in innate-like B1 B cells that also discretely express it. As in earlier work (Ehrhardt et al, 2003), we engineered a panel of chimeric receptor mutant constructs comprised of the extracellular and transmembrane portions of mouse FcγRIIB fused to different FCRL5 Y>F tail variants for transduction into the FcγR deficient IgG2a class-switched A20IIA1.6 B cell line (Zhu et al, 2013). This system permits a comparative analysis of downstream signaling pathways engendered by chimeric receptor/BCR co-engagement by using intact anti-mouse IgG versus BCR-only triggering using F(ab’)2 fragments (Okazaki et al, 2001).…”
Section: Functional and Regulatory Propertiesmentioning
confidence: 99%
“…We also showed that FCRL-5 binds to the conformational form of IgG, suggesting that FCRL-5 is a new type of receptor that may enable B cells to sense Ig quality (27). Overall, it is speculated that binding of FCRLs to these ligands guides the lymphocytes for appropriate differentiation through the regulation of BCR signaling (28). …”
mentioning
confidence: 99%
“…Similarly, the FCRL2 and FCRL5 molecules display inhibitory activity upon coligation with the BCR by a mechanism dependent on tyrosine phosphorylation and recruitment of the SHP-1 phosphatase (17,18). Interestingly, a recent study demonstrated that ligation of FCRL5 in viable motheaten mice lacking a functional SHP-1 phosphatase enhanced BCR signaling, whereas coligation of FCRL5 with the BCR on B lineage cells derived from Lyn 2/2 mice inhibited BCR signals (19). In contrast with the inhibitory activity of FCRL2, FCRL4, and FCRL5, FCRL1 functions as coactivator on human B lineage cells via a mechanism that remains to be elucidated (20).…”
mentioning
confidence: 99%